Effectiveness of the Dr. C.W.W. Kannangara's Education Reforms - Jayawardhana, Ananda (My University, 2012)
This article analyse Dr. C.W.W. Kannangara is reforms. Making educational opportunities, giving the monthly salary scheme, obtain rural education system, making school health programme. From 1931 to 1939, Preparing more educational opportunities development of schools, reforming of school curriculum, making human resource development of school level, teaching through mother language, establishment of central schools, giving free education, education converted to the poor people from elites.